2004
DOI: 10.1136/hrt.2003.010637
|View full text |Cite
|
Sign up to set email alerts
|

Isolated left ventricular apical hypoplasia: a new congenital anomaly described with cardiac tomography

Abstract: Objective: To describe cardiac tomography findings of an apparently new, presumably congenital, left ventricular (LV) abnormality noted consistently in three patients. Patients: Three patients presenting with non-specific symptoms including fatigue, shortness of breath, or chest discomfort were evaluated with cardiac tomography for cardiac structure and function. Results: Findings from the three patients were very similar: a truncated and spherical LV with abnormal diastolic and systolic function, invagination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
67
0
5

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(73 citation statements)
references
References 15 publications
1
67
0
5
Order By: Relevance
“…In this study 22 patients were reported in these literatures: Age: the minimum is 3-month-old [6], the maximum is 66-year-old [7], and the mean age is 29-year-old. Gender: Male: 9 [1,5,[7][8][9][10][11][12][13]; Female: 11 [1,[8][9][10][11][12][13][14][15][16][17][18][19][20] [3,[8][9][10][11][12][13][14]. As to the etiology of Isolated LVAH, it remained unclear.…”
Section: Resultsmentioning
confidence: 99%
“…In this study 22 patients were reported in these literatures: Age: the minimum is 3-month-old [6], the maximum is 66-year-old [7], and the mean age is 29-year-old. Gender: Male: 9 [1,5,[7][8][9][10][11][12][13]; Female: 11 [1,[8][9][10][11][12][13][14][15][16][17][18][19][20] [3,[8][9][10][11][12][13][14]. As to the etiology of Isolated LVAH, it remained unclear.…”
Section: Resultsmentioning
confidence: 99%
“…Many hypotheses have been formulated to explain in utero formation of this pathology but abnormal ventricular septation can be considered the most accepted. 1 Conversely, another interesting theory suggests that the LV could be divided into 3 distinct anatomic components, namely the inlet; the apical trabecular portion; and the outlet. In this context, isolated LVAH could be considered the expression of congenital malformation of the trabecular portion alone, while the relatively most common hypoplastic left heart syndrome involves all 3 entities.…”
Section: Images In Cardiovascular Medicine Baroni M Et Almentioning
confidence: 99%
“…(США) на основании сход-ных данных компьютерной и магнитно-резонансной томографии (МРТ) трех пациентов впервые описали врожденную изолированную гипоплазию верхушки левого желудочка (ИГВЛЖ) [1]. Для ИГЛЖ характерны: 1) сферическая форма ЛЖ со срезанной верхушкой и вы-буханием межжелудочковой перегородки (МЖП) вправо в сочетании с нарушением систолической функции ЛЖ; 2) замещение миокарда верхушки ЛЖ жировой тканью; 3) локализация папиллярных мышц на уплощенной верхушке ЛЖ; 4) удлиненный правый желудочек (ПЖ), обтекающий контур верхушки ЛЖ [1][2][3][4][5]. Patrianakos A.P.…”
unclassified
“…[1] и по на-стоящий момент опубликовано всего 26 сообщений, из них 24 англоязычные и 2 русскоязычные статьи, в кото-рых в основном представлены единичные клинические наблюдения или анализ диагностических и клинических находок у небольшой группы пациентов с ИГВЛЖ.…”
unclassified